Factors contributing to air pollution levels using factor analysis - Asmarini, Mohamed
The aims of this study is to determine the major factors and causes of air pollution levels within the four selected Malaysian air monitoring stations. The data were obtained from January 2008 to December 2012. The variables concerned are two meteorological factors (temperature and relative humidity) and four air pollutants (CO, PM10, O3 and NO2). The focus areas comprise of four different localities which are; Perai (S1- industrial), Shah Alam (S2-urban), Seberang Jaya (S3-suburban) and Jerantut (S4- control). Two statistical methods were selected to analyze the datasets which are descriptive statistical analysis and factor analysis. The descriptive statistical analysis showed that Perai recorded the highest concentrations of CO, O3 and NO2 while Seberang Jaya recorded the highest concentration of PM10. The results of the factor analysis showed that there were three factors at Perai, Shah Alam and Jerantut while two factors at Seberang Jaya. However, the combination of the components in each factors are different for every station. Nevertheless, it has a significant combination of the components at Perai where it can be categorized as an Organic Pollution Factor, Meteorological Factor and Fuel Factor. These results present a guideline to establish evaluations appropriate to pollution characteristics and classification systems for air quality monitoring stations in Malaysia.